National and worldwide environmental requirements in terms of the quality of automotive fuels - Kamiński , Arkadiusz (Studia Ecologiae et Bioethicae, 2015)
In the publication entitled „Modifications in European and Polish law implying changes in the production process, chemical composition and distribution of automotive fuels” the necessity and accuracy of implementing described changes in terms of the natural environment and human health were highlighted. In the current publication, which is the continuation of the previous one, the attention was paid to the environmental requirements implementation in national circumstances with regards to lead elimination, benzene content limitation, oxygen compounds limitation, sulfur limitations as well as with all issues concerning FAME.